Role of sulphur atoms on stress relaxation and crack propagation in monolayer MoS2. (8th August 2017) - Wang, Baoming; Islam, Zahabul; Zhang, Kehao; Wang, Ke; Robinson, Joshua; Haque, Aman
Abstract: We present in-situ transmission electron microscopy of crack propagation in a freestanding monolayer MoS2 and molecular dynamic analysis of the underlying mechanisms. Chemical vapor deposited monolayer MoS2 was transferred from sapphire substrate using interfacial etching for defect and contamination minimization. Atomic resolution imaging shows crack tip atoms sustaining 14.5% strain before bond breaking, while the stress field decays at unprecedented rate of 2.15 GPa Å −1 . Crack propagation is seen mostly in the zig-zag direction in both model and experiment, suggesting that the mechanics of fracture is not brittle. Our computational model captures the mechanics of the experimental observations on crack propagation in MoS2 . While molybdenum atoms carry most of the mechanical load, we show that the sliding motion of weakly bonded sulphur atoms mediate crack tip stress relaxation, which helps the tip sustain very high, localized stress levels.